Solitary metastatic deposit in the mandible from follicular thyroid carcinoma - Manevska, Nevena; Makazlieva, Tanja; Stojanoski, Sinisha; Vela, Ilir; Komina, Selim (Georg Thieme Verlag KG, 2020)
Follicular thyroid carcinoma (FTC) is the second most common cancer of the thyroid, after papillary carcinoma. Oral metastasis arising from FTC is very rare. Mandible is more commonly affected than maxilla, with the premolar—molar region being the most frequent site of metastasis. We present the case of a 68yearold female, with swelling in the region of the parotid gland, complaining of periodic rightsided pain in the temporomandibular joint, which occurred most often in the morning with numbness and pain, and difficulty in opening the mouth. After ultrasound and X-ray, the patient was operated and the pathohistological finding was in favor of metastasis of FTC. After 3 months, a total thyroidectomy was performed, and FTC was detected in the right thyroid lobe. Laboratory results were as follows: FT4 = 9.92 pmol/L, thyroid-stimulating hormone = 9.9 mIU/L, and hTG >300 μg/L. Bone scan showed no bone metastasis. Radioablation with 131I of 150 mCi was given to the patient, followed by substitutional therapy with levothyroxine. Mandible metastasis as a single skeletal deposit from follicular thyroid carcinomas is a rare clinical finding. Maxillofacial surgeons should consider and rule out thyroid pathology before performing operation of tumor formation in the mandible region. If feasible, surgical-based treatment options offer the best survival outcomes.
Keywords: follicular thyroid carcinoma; mandible metastasis; radioiodine